A Fed for Our Times: A Review Essay on 21st Century Monetary Policy by Ben Bernanke - Reichlin, Lucrezia (Journal of Economic Literature, 2023)
This essay reviews 21 st Century Monetary Policy: The Federal Reserve from the Great Inflation to COVID-19 by Ben Bernanke, a fascinating account of the evolution of the Fed since the 1950s, and a stalwart defense of the status quo: of the Fed’s remit, its independence, and the tools and practices it now uses to pursue its mandate. The essay supports many of Bernanke’s key points and brings the experience of the European Central Bank to illuminate them by contrast. However, it argues that the book understates the significance of the changes in institutional architecture that have emerged since the crisis. Questions that we thought had been settled are going to have to be addressed anew, albeit in slightly different guises. This will have implications for all aspects of economic governance. (JEL E31, E32, E52, E58, E62, N12, N22)